The impact of the SSIIa null mutations on grain traits and composition in durum wheat - Botticella, Ermelinda (Breeding science, 2016)
Starch represents a major nutrient in the human diet providing essentially a source of energy. More recently the modification of its composition has been associated with new functionalities both at the nutritional and technological level. Targeting the major starch biosynthetic enzymes has been shown to be a valuable strategy to manipulate the amylose-amylopectin ratio in reserve starch. In the present work a breeding strategy aiming to produce a set of SSIIa (starch synthases IIa) null durum wheat is described. We have characterized major traits such as seed weight, total starch, amylose, protein and β-glucan content in a set of mutant families derived from the introgression of the SSIIa null trait into Svevo, an elite Italian durum wheat cultivar. A large degree of variability was detected and used to select wheat lines with either improved quality traits or agronomic performances. Semolina of a set of two SSIIa null lines showed new rheological behavior and an increased content of all major dietary fiber components, namely arabinoxylans, β-glucans and resistant starch. Furthermore the investigation of gene expression highlighted important differences in some genes involved in starch and β-glucans biosynthesis